Optimizing Waste Routes with Cheapest Insertion and A-Star - Fadli, Ilham Dwi Reza; Romli, Moh. Ali (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Efficient waste management poses a significant challenge in many regions, particularly in optimizing waste collection routes. This research focuses on developing a web and mobile-based waste management application using the Cheapest Insertion Heuristic (CIH) algorithm to determine the most efficient collection routes. The application is built with the Flutter framework, integrates OpenStreetMap for mapping, and includes a notification feature for collection schedules. The dataset used includes waste bin locations, collection schedules, and real-time collection statuses. The primary objective is to create a system that minimizes travel distance and time for waste collecting vehicles. Testing results indicate that the application successfully enhances the efficiency of waste management routes. This application is expected to contribute to more effective waste management, increase public awareness regarding cleanliness, and support improved waste management systems in various regions.